Dynamics of Specific Vesicle-Substrate Adhesion: From Local Events to Global Dynamics - Reister-Gottfried, Ellen; Sengupta, Kheya; Lorz, Barbara Gertrud; Sackmann, Erich; Seifert, Udo; Smith, Ana-Suncana (Physical Review Letters, 2008)
We present a synergistic combination of simulations and experimental data on the dynamics of membrane adhesion. We show that a change in either the density or the strength of the bonds results in very different dynamics. Such behavior is explained by introducing an effective binding affinity that emerges as a result of the competition between the strength of the chemical bonds and the environment defined by the fluctuating membrane.
Keywords: MEMBRANES; CELLS; DIFFUSION; KINETICS; COMPLEX